Analisis Efektivitas Penggunaan E-Filing Bagi Wajib Pajak Pribadi dalam Pelaporan PPh Pasal 21 pada Karyawan PT Tirta Mahakam - Andi Indrawati3, Cindi Afriyani1, Titin Ruliana2 (EKONOMIA, 2021)
The purpose of this research is to know and analyze the effectiveness of the use of e-filing for personal taxpayers in reporting Pph article 21 to employees of PT. Tirta Mahakam. In accordance with the objectives of this study, the subject matter put forward "Is the use of e-filing for personal taxpayers in the reporting of Pph Article 21 Tax at PT Tirta Mahakam effective" "Theory basis used is a theoretical basis concerning the effectiveness of using e-filing and reporting of Pph 21 to employees of PT. Tirta Mahakam. Based on these main problems, the following hypothesis is proposed: ‘The use of e-filing for personal taxpayers in reporting Pph 21 taxes for employees of PT. Tirta Mahakam is considered ineffective based on the effectiveness assessment criteria ''.Based on the results of the analysis previously stated, it can be seen that the effectiveness of using e-filing in tax reporting Pph 21 for employees of PT. Tirta Mahakam has been running quite well, this is evidenced by the results of the analysis which got a relative value of 79% on the effectiveness measurement criteria which is categorized as "effective". Even though there are still some employees who do not understand the e-filing system, the awareness of taxpayers to report the Annual Tax Return and the lack of the KPP Pratama to provide more active socialization so that employees understand e-filing and its benefits